EFFECTS OF EDUCATIONAL INTERVENTION ON SELF CARE MANAGEMENT AMONG BURN PATIENTS (The Research of Medical Science Review, 2024)
Background: Burn injuries can be very dangerous and cause serious physical and emotional problems. People who are burned not only have to deal with their injuries but also with how they look after the burns. It's really tough for them. Especially if the burns are severe, they might feel really upset and suffer a lot, both in their body and mind. Having support from friends and family is super important to help them feel better about themselves. Family members should learn how to help, and the patients themselves need to take better care of their health. This study's results could be a helpful guide for others going through similar issues.Objective: To investigate the effect of educational intervention on self care management among burn patientsMethod: A quasi-experimental design was carried out at the Pak-Italian Modern Burn Center in Multan, involving 108 burn patients. Information was gathered using the Functional Assessment for Burns sheet. The collected data underwent analysis using methods like Chi-Square and paired t-tests, with significance indicated as p<0.05. The results were presented in the form of a frequency table.Result: Most of the patients (60.2%) were men between 32 and 45 years old, living in cities (52.8%). About half of them were single (48.1%), and 56.6% had burns on their face that went down to their chest. Before the education, patients with burn injuries scored an average of 16.20+3.42 for self-care, but after the education, it went up to 32.13+5.41, and this change was very significant with a value of p=0.000.Conclusion: This study revealed that teaching patients at the burn unit about taking care of themselves and coping with changes using exercises and rehabilitation methods was really helpful. By involving patients more in their own care, their ability to take care of themselves improved a lot. This made a big difference in how well burn patients managed their own care.